2023
DOI: 10.3390/app13074623
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reagent Ion-Time-of-Flight-Mass Spectrometric Investigations of the Intravenous Anaesthetic Propofol and Its Major Metabolite 2,6-Diisopropyl-1,4-benzoquinone

Abstract: The first detailed selected reagent ion-time-of-flight-mass spectrometric fundamental investigations of 2,6-diisopropylphenol, more commonly known as propofol (C12H18O), and its metabolite 2,6-diisopropyl-1,4-benzoquinone (C12H16O2) using the reagent ions H3O+, H3O+.H2O, O2+• and NO+ are reported. Protonated propofol is the dominant product ion resulting from the reaction of H3O+ with propofol up to a reduced electric field strength (E/N) of about 170 Td. After 170 Td, collision-induced dissociation leads to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The VUV light ion source emits photons with an energy of 10.6 eV to softly ionize volatile organic compounds in gas samples rapidly. The study by Chawaguta et al showed that soft chemical ionization mass spectrometry can detect propofol and its major metabolites in real time with high levels of confidence by monitoring specific different product ions [3]. The photoionization limits the formation of fragment ions, facilitating the facile separation of propofol from other volatiles present in exhaled breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VUV light ion source emits photons with an energy of 10.6 eV to softly ionize volatile organic compounds in gas samples rapidly. The study by Chawaguta et al showed that soft chemical ionization mass spectrometry can detect propofol and its major metabolites in real time with high levels of confidence by monitoring specific different product ions [3]. The photoionization limits the formation of fragment ions, facilitating the facile separation of propofol from other volatiles present in exhaled breath.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional technique for off-line breath analysis is gas chromatography-mass spectrometry (GC-MS), which is operation-complicated and timeconsuming. [1] In the last two decades, different mass spectrometers have been developed to achieve the goal of on-line propofol monitoring, such as proton transfer reaction mass spectrometry, [2,3] selected ion flow tube mass spectrometry [4] and ion molecule reaction mass spectrometry (IMR-MS) [5]. However, these instruments still have disadvantages such as loud noise and large volume [6].…”
Section: Introductionmentioning
confidence: 99%